Penerapan Akad Pembiayaan Murabahah Di BMT Sahara Kauman Tulungagung - Yeva Putri Wulandari; Fatkhur Rohman Albanjari (Universitas Muhammadiyah Ponorogo, 2021)
In financial institutions, especially in BMT Sahara Kauman, there is a financing agreement that is often used by members for financing, namely the murabahah contract. The members choose the murabahah financing contract because it is considered to have low risk. The objectives of this study are (1) how to implement a murabahah financing agreement at BMT Sahara Kauman, (2) the mechanism for implementing a murabahah financing agreement at BMT Sahara Kauman. This study uses a qualitative descriptive method. From the author's observations, there are two conclusions, namely first, the application of Murabahah financing at BMT Sahara Kauman, is engaged in micro- economics, and of course in a halal business. Second, the mechanism for the application of Murabahah financing at BMT Sahara Kauman, in general, in accordance with the existing rules in the principles of Sharia Economics.Â